2019
DOI: 10.1080/21691401.2019.1666861
|View full text |Cite|
|
Sign up to set email alerts
|

Sinomenine restrains breast cancer cells proliferation, migration and invasion via modulation of miR-29/PDCD-4 axis

Abstract: Sinomenine (Sino) is diffusely applied in heal rheumatoid arthritis and neuralgia. Howbeit, the activities of Sino in breast cancer cells remain confused. The research attempted to probe the anti-tumor function of Sino in breast cancer cells and divulge the feasible molecular mechanism. Sion at the 1-16 lM concentrations was exploited for the exposure of MDA-MB-231 or MCF7 cells, and cell growth, migration, invasion, cell cycle-relevant and apoptosis-correlative factors were estimated. Micro RNA (miR)-29 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…As expected, sinomenine can affect the growth and apoptosis of RB cells in vitro; moreover, sinomenine also lead to decreased migration as well as invasion ability of the RB cells, and the effects of sinomenine were in a dose-dependent manner. These results were consistent with its anti-tumor behaviors in other cancers 9,[12][13][14] . Like any other type of cancer cell, RB cells 7,18) were characterized by the uncontrolled growth and increased migration and invasion ability of the tumor cells, the above observations suggested that sinomenine can inhibit the growth and metathesis of WERI-RB-1 and Y79 cells in vitro, suggesting that sinomenine can exert anti-tumor effects in RB.…”
Section: Effect Of Sinomenine Treatment On the Migration As Well As Isupporting
confidence: 87%
See 1 more Smart Citation
“…As expected, sinomenine can affect the growth and apoptosis of RB cells in vitro; moreover, sinomenine also lead to decreased migration as well as invasion ability of the RB cells, and the effects of sinomenine were in a dose-dependent manner. These results were consistent with its anti-tumor behaviors in other cancers 9,[12][13][14] . Like any other type of cancer cell, RB cells 7,18) were characterized by the uncontrolled growth and increased migration and invasion ability of the tumor cells, the above observations suggested that sinomenine can inhibit the growth and metathesis of WERI-RB-1 and Y79 cells in vitro, suggesting that sinomenine can exert anti-tumor effects in RB.…”
Section: Effect Of Sinomenine Treatment On the Migration As Well As Isupporting
confidence: 87%
“…In clinical field, sinomenine has been proved to play protective roles in cardiovascular system, immune system, as well as other tissues and organs 10,11) . So far, sinomenine has been regarded as an anti-tumor reagent for the treatment of many types of cancers, for example, gastric cancer, breast cancer and so on [12][13][14] . However, the roles as well as underlying mechanisms of sinomenine in regulating the progression of RB has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-29 has been related to types of cancer. miR-29 restrains proliferation, migration, and invasion in breast cancer cells through downregulating PDCD-4 [23]. miR-29 targeting PTEN inhibits proliferation and migration of osteosarcoma cells [24].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-tumor activity of sinomenine was well studied in gastric, 21,22 breast, 23 prostate, 24 cervical 25 cancer, renal cell carcinoma, 26 and glioma. 27 Inhibition of cell cycle progression, 27 angiogenesis, 26 metastasis, 28 and induction of apoptosis or autophagy are involved in sinomenine-mediated anti-tumor activity.…”
Section: Discussionmentioning
confidence: 99%